Characterization and Prevalence of Clindamycin Resistance Staphylococcus aureus from Clinical samples of National Medical College and Teaching Hospital, Nepal - AMRULLAH SHIDIKI; BIJAY RAJ PANDIT; ASHISH VYAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Clindamycin is the drug of choice for the treatment of severe form of skin, soft tissue, and blood infections caused by resistant Staphylococcus aureus in the form of methicillin-resistant S. aureus (MRSA) and erythromycin-resistant S. aureus. In this research, we determine the susceptibility pattern of isolated S. aureus strains against antibiotics and the prevalence of resistant S. aureus in the form of MRSA, inducible clindamycin-resistant S. aureus (inducible macrolide-lincosamide-streptogramin B [iMLSB]) and constitutive clindamycin-resistant S. aureus (cMLSB). Methods: A total of 310 isolated S. aureus among 2000 different clinical samples were subjected to oxacillin (1 μg) as per the Kirby-Bauer disk diffusion method for MRSA. Clindamycin-resistant either in the form of iMLSB or cMLSB was determined through double disk diffusion method or D-test by use erythromycin (2 μg) and clindamycin (15 μg) as per the CLSI guidelines. Results: Out of total S. aureus, MRSA and methicillin-sensitive S. aureus (MSSA) were 78.06% and 20.64%, respectively. This study showed that iMLSB and cMLSB were 34.19% and 23.22%. Both iMLSB and cMLSB were found more among MRSA than MSSA (43.80%, 26.85% and 40.62%, 10.93%), respectively. Conclusion: This study helps for the characterization of different resistant strains of S. aureus along with the determination of the prevalence rate of these mutant forms causing nosocomial infections.